DAMPAK KONFLIK RUSIA-UKRAINA TERHADAP KERJASAMA IMPOR GANDUM UKRAINA DENGAN INDONESIA - Pamungkas, Putra Rida; ', Pazli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
The conflict between Russia and Ukraine has had a significant impact on wheat imports to Indonesia and trade cooperation between the two countries. Although economic cooperation between Ukraine and Indonesia has been established in recent years, tensions between Russia and Ukraine have resulted in serious disruption to these relations. This research uses a qualitative literature study method by collecting data from books, academic journals, official documents, laws, and related internet sources, namely research on the conflict between Russia and Ukraine and its effect on wheat cooperation with Indonesia. The results of this research are that the Russia-Ukraine conflict has an impact on Indonesian wheat imports and trade cooperation between the two countries. Despite economic cooperation, this conflict disrupted the relationship. Indonesia, the largest wheat importer, was affected by supply disruptions, price increases and shipping disruptions. The government needs to establish a flexible and efficient import policy and support domestic wheat farming. Collaboration with Ukraine and other parties is needed to increase Indonesia's food security. Keywords: Russia-Ukraine conflict, wheat imports, economic cooperation